2006
DOI: 10.1162/jocn.2006.18.12.2030
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Proficiency on Syntactic Second-language Processing of German and Italian: Evidence from Event-related Potentials

Abstract: Abstract& The present study investigated the role of proficiency in late second-language (L2) processing using comparable stimuli in German and Italian. Both sets of stimuli consisted of simple active sentences including a word category violation, a morphosyntactic agreement violation, or a combination of the two. Four experiments were conducted to study high-and lowproficiency L2 learners of German as well as high-and lowproficiency L2 learners of Italian. High-proficiency L2 learners in both languages showed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

29
237
6
4

Year Published

2007
2007
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 254 publications
(276 citation statements)
references
References 43 publications
29
237
6
4
Order By: Relevance
“…Steinhauer et al interpreted these results as supporting the possibility of native-like L2 processing among highly proficient adult learners. At the same time, given the greater typological similarity between English and French than between English and Chinese, the lack of a LAN for the highly proficient Chinese speakers raised the possibility that L1 transfer modulates nativelikeness of processing (for similar findings, see Foucart and Frenck-Mestre 2011;Rossi et al 2006). Recent work has also linked different L2 ERP effects to structure-specific L2 proficiency.…”
Section: Event-related Potentials and L2 Proficiencymentioning
confidence: 99%
“…Steinhauer et al interpreted these results as supporting the possibility of native-like L2 processing among highly proficient adult learners. At the same time, given the greater typological similarity between English and French than between English and Chinese, the lack of a LAN for the highly proficient Chinese speakers raised the possibility that L1 transfer modulates nativelikeness of processing (for similar findings, see Foucart and Frenck-Mestre 2011;Rossi et al 2006). Recent work has also linked different L2 ERP effects to structure-specific L2 proficiency.…”
Section: Event-related Potentials and L2 Proficiencymentioning
confidence: 99%
“…More recently though, L2 syntactic comprehension of, for example, phrase structure constraints and verb agreement has been investigated with online measures such as ERPs (Hahne, 2001;Rossi, Gugler, Hahne, & Friederici, 2006;Tokowicz & MacWhinney, 2005;Weber-Fox & Neville, 1996;Weber-Fox & Neville, 2001). The use of such a temporally fine-grained measure allows investigating how L2 speakers of a language process syntactic information while sentence comprehension unfolds in time.…”
Section: Introductionmentioning
confidence: 99%
“…Phrase structure violations resulted in a P600. In a recent study by Rossi et al (2006) the authors propose that the variable results in L2 syntactic processing may not just depend on AoA, but also on the level of achieved L2 proficiency. Comparing the ERPs of late high and low proficient German and Italian learners of Italian and German, respectively, they reported a comparable syntactic processing pattern for both phrase structure and agreement violations in late high proficient learners.…”
Section: Introductionmentioning
confidence: 99%
“…The same was not true for beginning bilinguals, when the prime was in L2 and the target in the first language (L1). Rossi, Gugler, Friederici, and Hahne (2006) reported that highly proficient late L2 learners showed the same event-related potential responses to syntactic violations in sentences as L1 speakers, but this was not true for low-proficiency L2 learners, who had a qualitatively different response to the violations. Other neuroscientific research has indicated that the pattern of brain activation is modulated by L2 proficiency.…”
mentioning
confidence: 98%